The Role of Central and Peripheral Vision in Expert Decision Making. (June 2013) - Ryu, Donghyun; Abernethy, Bruce; Mann, David L; Poolton, Jamie M; Gorman, Adam D
The purpose of this study was to investigate the role of central and peripheral vision in expert decision making. A gaze-contingent display was used to selectively present information to the central and peripheral areas of the visual field while participants performed a decision-making task. Eleven skilled and eleven less-skilled male basketball players watched video clips of basketball scenarios in three different viewing conditions: full-image control, moving window (central vision only), and moving mask (peripheral vision only). At the conclusion of each clip participants were required to decide whether it was more appropriate for the ball-carrier to pass the ball or to drive to the basket. The skilled players showed significantly higher response accuracy and faster response times compared with their lesser-skilled counterparts in all three viewing conditions, demonstrating superiority in information extraction that held irrespective of whether they were using central or peripheral vision. The gaze behaviour of the skilled players was less influenced by the gaze-contingent manipulations, suggesting they were better able to use the remaining information to sustain their normal gaze behaviour. The superior capacity of experts to interpret dynamic visual information is evident regardless of whether the visual information is presented across the whole visual field or selectively to either central or peripheral vision alone.